MANAGEMENT OF FEMALE INFERTILITY (VANDHYATVA) W.S.R. TO ANOVULATORY FACTOR - A CLINICAL CASE STUDY - kour Jatinder,; Donga Shilpa.B., (International Journal of Applied Ayurved Research, 2016)
Now a day’s prevalence of Infertility having anovulation is increased in women of reproductive age group. Etiology is due to defective life style and hormonal imbalance. Female-factor infertility is most commonly caused by lack of ovulation (i.e. the development and release of eggs from the ovary). Ovulation problems can be caused by hormonal deficiencies or lifestyle factors, such as obesity, alcohol intake, or being severely underweight. Fallopian tube blockage is another common cause of infertility .So here in this case study we selected a case of primary infertility because of anovulation.In modern science there are treatments like Clomiphene Citrate, IVF(In-vitro fertilization), GIFT(Gamete intra fallopian transfer)etc. available for ovulation induction but all have unsatisfactory results, enormous expenses, lots of side effects and complications. So there is a great scope of research to find out safe, potent, less costly and effective remedies from Ayurveda for the management of Vandhyatva( Female Infertility) .According to ayurvedic classics Artav is the Updhatu of Rasa Dhatu and again Artava has all the qualities of Shonita(Rakata). Under Artava;menstrual blood and Ovum are included. Drugs used for the treatment had Rasa & Raktshodhan properties mentioned by charak acharya and so also helps in the formation of raja(ovum) and normalization of menstrual cycle. So one patient has been selected having primary infertility for two years with painful and scanty menses.So here,in this case we did management with Matra basti of Shatpushpadi taila.